Comparative study of the electrochemical behaviour of glucose and other compounds of biological interest - Fernández Lorenzo de Mele, Mónica Alicia (1982)
The electro-oxidation of glucose and related compounds was studied in phosphate buffered media using a smooth platinum working electrode at different temperatures. A comparative analysis of the electrochemical behaviour of glucose and gluconic acid was made. Different electrochemical responses were found in the hydrogen adatom and in the PtO layer formation potential regions. Potentiostatic and potentiodynamic measurements with inositol, fructose, xylose, arabinose and glucose-1-phosphate were also performed in an attempt to find a relation between the electrochemical behaviour and the structural characteristics of these molecules. Our results suggest that the hemiacetalic group of the glucose molecule seems to play an important role in the electro-oxidation process. The electro-oxidation order of the different carbohydrates and derivatives resembles to some extent the electrochemical conversion order already established for other compounds.